Revisiting English Language Teaching (ELT) Curriculum Design: How Appropriate is Bangladesh Higher Secondary Level National ELT Curriculum as a Learner-Centred One? - Ali, Md Maksud (IIUC Studies, 2012)
ELT curriculum design has seen several transformations overtime, especially with the changing views on the educational ideologies and philosophies in the western world. As far as teaching English in an English as a Second/Foreign language (ESL/EFL) context is concerned, it is often suggested that the ESL or the EFL education should be acculturalized as to be responsive to a particular group of people, and that again refers to the need for a national curriculum for ELT in an EFL country. Thus, in designing an ELT curriculum in an ESOL context, the designers need to examine not only whether the curriculum is responsive to the needs of a group of learners but also if it is culturally appropriate in that context or not. Following a qualitative case study research method, this paper examines the extent to which the Higher Secondary ELT national curriculum in Bangladesh is responsive to the socio-cultural needs and the needs of the learners. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12494 IIUC Studies Vol.7 2011: 283-296